The Effect of Work Compensation on Intention to Stay in the Hotel Industry During the COVID 19 Pandemic with Job Embeddedness as Mediation: (Study on Hotel Management Graduates, Universitas Negeri Padang) - Feri Ferdian; Youmil Abrian; Hijriyantomi Suyuthie; Kasmita Kasmita; Rizki Amelia Sinensis (Jurnal Organisasi dan Manajemen, 2022)
Purpose - This study aimed to analyze the effect of work compensation on the intention to stay in the hotel industry during the COVID 19 pandemic mediated by job embeddedness. Methodology - A quantitative approach was used on 670 graduates who majored in hotel management based on purposive sampling. The sample size was estimated at 30% of the total population (201 graduates) working in the hotel industry, collecting 145 respondents. Furthermore, the data were analyzed using the Partial Least Square Structural Equation Modelling (PLS-SEM). Findings - The results showed that work compensation affected the graduates’ intentions to stay and job embeddedness in the hotel industry during the COVID 19 pandemic. Job embeddedness affected the intention to stay and mediated its relationship with compensation. Originality - The effect of work compensation on graduates’ intention to stay in the hotel industry during the pandemic was investigated to gain a better understanding. Furthermore, testing job embeddedness as a mediator of the relationship between work compensation and staying intentions produced a new theoretical understanding. Novelty in this study found that graduates still have the intention to stay in the hotel industry due to the job embeddedness that has been formed as a result of the work compensation received which is still in line with their expectations even in the conditions of the COVID 19 pandemic.